Optimalisasi Jaringan MikroTik Dengan Menggunakan Load Balancing PCC dengan Pendekatan PPDIOO - Ahmadi, Meisandi Naufal; Risqiwati, Diah; Muthohirin, Bashor Fauzan (Institut Teknologi Garut, 2025)
The need for a stable and high-performance network is essential to support real-time data transmission. One common challenge faced is the effective management of two or more internet connections to avoid bottlenecks on a single link. This study aims to optimize network performance by implementing the Load Balancing PCC (Per Connection Classifier) method on Mikrotik routers to evenly distribute traffic load across two available ISP links. The research methodology used is PPDIOO (Prepare, Plan, Design, Implement, Operate, Optimize), an approach that encompasses all network management activities. The testing environment is simulated using PNETLab, with performance monitoring conducted using tools such as Zabbix Server Monitoring and Speedtest.net. The parameters tested include Quality of Services such as throughput, response time, bandwidth utilization, and traffic load distribution across each ISP link. The test results show that the application of the PCC method significantly improves network performance. The average throughput increased from 1.49 Mbps to 2.08 Mbps, response time decreased from 3.6 ms to 1.6 ms, and download bandwidth utilization increased from 0.43 Mbps to 0.96 Mbps. Furthermore, the traffic load, which was initially concentrated on a single ISP link, was successfully distributed evenly across both links, demonstrating that PCC load balancing is effective in balancing connections. Therefore, this method is highly recommended for network implementations that require high efficiency and stability in traffic management.